Non-aqueous electrolyte and lithium ion battery containing same
By using additives A and B with specific structures in lithium-ion batteries, synergistically suppressing electrolyte decomposition and interface impedance, the stability problem of high-nickel positive electrode materials is solved, the circulation and storage performance of lithium-ion batteries is improved, and the high-quality Energy density and stability enhance the safety and reliability of the battery.
Patent Information
- Application Number
- CN202411402505.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2024-12-17
AI Technical Summary
High-nickel ternary cathode material has stability problems during the circulation and storage process of lithium-ion batteries, resulting in electrolyte decomposition, gas generation and side reactions, affecting battery performance and safety.
A non-aqueous electrolyte is used, which contains additive A and additive B of specific structures. The phenylphosphine-containing groups in additive A are chelated with nickel ions, and the difluorophosphine-based groups in additive B are complexed with metal ions to inhibit The electrolyte decomposes and interface impedance form a stable SEI film, which works synergistically to improve battery circulation and storage performance.
Effectively reduce the cycle impedance of lithium-ion batteries, extend life, improve high-temperature storage performance, achieve high energy density and stability, and enhance the safety and reliability of the battery.
Smart Images

Figure BDA0005075656550000021 
Figure BDA0005075656550000081 
Figure BDA0005075656550000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a non-aqueous electrolyte and a lithium ion battery containing the same. Background Art
[0002] The continued prosperity of new energy vehicles has promoted the rapid development of the entire lithium battery industry. Although the acceptance of lithium batteries in low-end markets such as energy storage and two-wheeled vehicles is not high, lithium-ion batteries have performed well in the power sector and 3C digital fields. Their unique performance and wide range of application scenarios make them an indispensable energy solution for modern society.
[0003] Lithium-ion batteries have significant advantages in energy density, which makes them highly efficient in energy storage and utilization in various applications. However, with the increasing shortage of lithium mineral resources, for countries like China, which do not have abundant lithium mineral resources, how to maximize the utilization of lithium is a key issue facing the lithium battery industry chain in the current market.
[0004] To improve the performance of lithium batteries, we need to start from multiple aspects. First: Improve safety performance: Battery safety issues are crucial in the new energy vehicle industry. Safety performance is the primary issue related to the vigorous development of lithium batteries. The explosion and combustion of batteries restrict the development of lithium batteries, and the development of new electrolyte materials and diaphragm materials is an important direction to improve battery safety performance. Second: Increase energy density and power density: Improving the energy density and power density of batteries can increase the cruising range and acceleration performance of new energy vehicles. This requires the development of electrode materials, electrolyte materials and diaphragm materials with high energy density and high power density. At the same time, optimizing battery structure and design is also key. High nickel positive electrode materials and silicon-based negative electrodes are new research hotspots in the industry, but their stability issues still need to be solved. Third: Improve cycle performance: Improving the cycle performance of batteries can extend the service life of batteries, reduce the frequency of battery replacement, and thus reduce the cost of use. This requires the development of electrode materials, electrolyte materials and diaphragm materials with high stability and long life.
[0005] The high nickel content in the high-nickel ternary positive electrode material will make the stability of the positive electrode plate worse. During the cycle and storage process, the contact interface between the electrode and the electrolyte is not stable enough, causing the electrolyte to continuously decompose. This will cause the battery to generate a large amount of gas during the cycle and storage process, further triggering side reactions and causing the battery to malfunction; at the same time, the byproducts of oxidative decomposition will cause the SEI film to continue to thicken, increase the interface impedance and make the battery worse.
[0006] Therefore, in order to inhibit the decomposition and gas production of the electrolyte, reduce the battery impedance, and thus improve the performance and reliability of lithium-ion batteries, it is of great significance to develop a new type of lithium-ion battery electrolyte. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a non-aqueous electrolyte and a lithium-ion battery containing the same. The non-aqueous electrolyte can effectively improve the cycle performance and storage performance of the high-nickel system, achieve the goal of high energy density of the battery cell, and is suitable for lithium-ion batteries with high-nickel positive electrode materials.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a non-aqueous electrolyte, comprising an electrolyte, a non-aqueous organic solvent and an additive, wherein the additive comprises an additive A and an additive B, wherein the additive A has a structure represented by formula 1, and the additive B has a structure represented by formula 2:
[0010]
[0011] The dotted lines represent the interactions between atoms.
[0012] The non-aqueous electrolyte of the present invention contains additive A and additive B at the same time, and the two play a synergistic role, which can not only reduce the cycle impedance of the lithium-ion battery and improve its cycle life, but also reduce the gas generation of the lithium-ion battery during storage and improve its high-temperature storage performance. That is, by adding specific additives A and additive B at the same time, the cycle performance and storage performance of the high-nickel system can be effectively improved, thereby achieving the goal of high energy density of the battery cell.
[0013] In the present invention, the introduction of the phenylphosphine group in the additive A can react with the Ni dissolved from the positive electrode. 2+ The electron-rich P atom in the group can provide a shared electron pair to form a stable Ni 2+ It is easy to form electronic ligands to achieve accurate capture of nickel ions, preventing the generation of side reactions related to nickel. According to Fick's first law, it can delay the metal ions (not limited to Ni) in the circulation process. 2+) is continuously dissolved, reducing the lithium-nickel mixing phenomenon to a certain extent, and participating in the film formation of positive and negative electrodes, inhibiting the decomposition of the electrolyte. The difluorophosphorus group in additive B can complex the decomposed metal ions in the positive electrode material, reduce the damage to the negative electrode, and effectively reduce the interface impedance; the tertiary amine cation can induce the formation of SEI containing Li3N fast ion transmission on the negative electrode surface, improving the battery cycle stability; at the same time, the lithium difluorophosphate group in additive B undergoes oxidation reaction before the solvent EC, and can form a dense and stable SEI interface film on the graphite negative electrode, and the inorganic components such as LixPOyFz in the interface film increase, while the organic carbonate components decrease. For the positive electrode / electrolyte interface phase (CEI), additive B can greatly increase the content of LiF on the interface, inhibit the positive electrode / electrolyte side reaction and reduce the interface impedance, and form a high content of PO substances on the positive electrode side, which can also inhibit the side decomposition of the solvent. Additive A can inhibit the dissolution of metal ions in the positive electrode material, and additive B can reduce the impedance of the battery and stabilize the SEI and CEI of the interface. The synergistic effect of the two can make the battery cycle stably and reduce the capacity decay.
[0014] Preferably, based on the mass of the non-aqueous electrolyte being 100%, the mass percentage of the electrolyte is 2-22%, for example, 2%, 4%, 6%, 8%, 10%, 13%, 15%, 18%, 20% or 22%, etc.
[0015] Preferably, the electrolyte is a lithium salt.
[0016] Preferably, the lithium salt comprises lithium hexafluorophosphate.
[0017] Preferably, based on the mass of the non-aqueous electrolyte being 100%, the mass percentage of the non-aqueous organic solvent is 75-94%, for example, it may be 75%, 78%, 80%, 82%, 85%, 88%, 90%, 92%, or 94%.
[0018] Preferably, the non-aqueous organic solvent comprises a carbonate organic solvent and / or a carboxylate organic solvent.
[0019] Preferably, the carbonate organic solvent includes cyclic carbonate and / or chain carbonate.
[0020] Preferably, the cyclic carbonate includes any one of ethylene carbonate (EC), propylene carbonate (PC) or butylene carbonate (BC) or a combination of at least two thereof.
[0021] Preferably, the linear carbonate includes any one of diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) or methyl propyl carbonate (MPC), or a combination of at least two thereof.
[0022] Preferably, the carboxylate organic solvent includes any one of ethyl propionate, propyl propionate, ethyl acetate, ethyl butyrate, methyl acetate, propyl acetate, methyl propionate or γ-butyrolactone, or a combination of at least two thereof.
[0023] In the present invention, by compounding cyclic carbonate and chain carbonate in a certain ratio as a non-aqueous organic solvent, it is beneficial to improve the overall dielectric constant of the electrolyte, and can ensure that the obtained non-aqueous electrolyte has a low viscosity and good wettability on the surface of the lithium ion battery pole piece, thereby ensuring the good operation of the lithium battery. Exemplarily, the non-aqueous organic solvent system selected in the present invention is EC:EMC=3:7 (volume ratio). At this time, by compounding with specific electrolytes and additives, the prepared lithium ion battery can have excellent electrochemical properties and stable performance.
[0024] Preferably, based on the mass of the non-aqueous electrolyte as 100%, the mass percentage of the additive A is 0.2-4%, for example, it can be 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.5%, 2%, 3% or 4%, etc., preferably 0.2-2%, and more preferably 0.4-1.5%.
[0025] Preferably, based on the mass of the non-aqueous electrolyte as 100%, the mass percentage of the additive B is 0.2-4%, for example, it can be 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.5%, 2%, 3% or 4%, etc., preferably 0.2-2%, and more preferably 0.4-1.5%.
[0026] In the present invention, the addition of a specific content of additive B can be well compounded with additive A, and the two play a synergistic role, which can significantly reduce the cycle impedance of the lithium-ion battery and improve its high-temperature storage performance. When the content of additive B is less than 0.2%, the formed interface film is not stable enough; when its content is higher than 4%, the battery impedance is large, affecting the battery performance; based on the mass of the non-aqueous electrolyte as 100%, when the content of additive B is 0.4-1.5%, the comprehensive performance of the lithium-ion battery prepared is better, so that the lithium-ion battery not only has a good room temperature capacity retention rate and a high high temperature capacity retention rate, thereby reducing the cycle impedance of the lithium-ion battery, and then enhancing the battery's cycle performance; but also improves the high-temperature storage gas production of the battery, thereby greatly suppressing the volume expansion phenomenon of the lithium-ion battery during storage, and then improving its high-temperature storage performance.
[0027] Furthermore, in the present invention, the mass ratio of additives A and B is (0.5-2.5):1 (for example, it can be 0.5:1, 0.8:1, 1:1, 1.2:1, 1.4:1, 1.5:1, 1.8:1, 2:1 or 2.2:1, etc.), and when the mass ratio of the two is 1:1, the synergistic effect of the two is optimal, and the lithium ion battery prepared therefrom has excellent room temperature capacity retention rate, higher high temperature capacity retention rate and lower high temperature gas storage and production volume expansion rate.
[0028] Preferably, the additive further includes a lithium salt additive.
[0029] Preferably, based on the mass of the non-aqueous electrolyte being 100%, the mass percentage of the lithium salt additive is 0.2-3.0%, for example, it may be 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.5%, 2%, or 3%.
[0030] Preferably, the lithium salt additive includes any one or a combination of at least two of lithium difluorosulfonimide (LiFSi), lithium difluorooxalatoborate (LiODFB), lithium tetrafluoroborate (LiBF4), bis(oxalatoborate) (LiBOB), lithium difluorophosphate (LiPO2F2) or lithium difluorobis(oxalatophosphate) (LiDFOP).
[0031] In the present invention, the use of lithium salt additives can effectively improve the capacity retention rate and cycle life of the battery, and can effectively broaden the operating temperature range of the lithium-ion battery; at the same time, the lithium salt additive can also take precedence over the formation of inorganic LiF, thereby further reducing the interface impedance.
[0032] Preferably, the additives include other additives.
[0033] Preferably, based on the mass of the non-aqueous electrolyte being 100%, the mass percentage of the other additives is 0.5-11.6%, for example, it may be 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 5%, 8%, 10% or 11%, etc.
[0034] Preferably, the other additives include any one of vinylene carbonate (VC), 1,3-propane sultone (PS), fluoroethylene carbonate (FEC), vinyl ethylene sulfate (ES), diethylene sulfate (DTD), methylene methanedisulfonate (MMDS), vinylene carbonate (VEC), tris(trimethylsilyl) phosphate (TMSP), and tris(trimethylsilyl) borate (TMSB), or a combination of at least two thereof.
[0035] In a second aspect, the present invention provides a lithium-ion battery, comprising a battery cell and an electrolyte, wherein the battery cell comprises a positive electrode, a negative electrode and a separator, wherein the separator is arranged between the positive electrode and the negative electrode, and the electrolyte is the non-aqueous electrolyte described in the first aspect.
[0036] Preferably, the positive electrode includes a positive electrode active material, a conductive agent and a binder.
[0037] In the present invention, the conductive agent and the binder in the positive electrode are both conventionally selected in the art.
[0038] Preferably, the negative electrode plate comprises a negative electrode active material.
[0039] Preferably, the material of the diaphragm includes any one of polyethylene, polypropylene or a composite ceramic membrane, or a combination of at least two of them.
[0040] Preferably, the positive electrode active material comprises LiNi x Co y Mn z L (1-x-y-z) O2 and / or LiNi x' L' y' Mn (2-x'-y') O4;
[0041] Wherein, L is any one of Al, Sr, Mg, Ti, Ca, Zr, Zn, Si or Fe, or a combination of at least two thereof;
[0042] 0.5≤x≤1, for example, x can be 0.5, 0.6, 0.7, 0.8, 0.9 or 1, etc.; 0≤y<1, for example, y can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9, etc.; 0≤z≤1, for example, z can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 , 0.9 or 1, etc.; 0<x+y+z≤1; 0<x'≤1, for example, x' can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1, etc.; 0.01≤y'≤0.2, for example, y' can be 0.01, 0.02, 0.05, 0.08, 0.1, 0.12, 0.15, 0.18 or 0.2, etc.
[0043] L' is any one of Co, Al, Sr, Mg, Ti, Ca, Zr, Zn, Si or Fe, or a combination of at least two thereof.
[0044] Preferably, the negative electrode active material includes any one of natural graphite, artificial graphite, soft carbon, hard carbon, mesophase carbon microspheres, graphene, graphyne, metallic lithium, nanocarbon, carbon nanotubes, elemental silicon, silicon oxide compounds, silicon / copper oxide complexes, AG complexes, silicon alloys, elemental tin, tin oxide compounds, tin-carbon complexes, tin alloys, or lithium titanate, or a combination of at least two thereof.
[0045] Compared with the prior art, the present invention has at least the following beneficial effects:
[0046] (1) The non-aqueous electrolyte provided by the present invention comprises an additive A and an additive B of a specific structure. The two additives cooperate with each other to exert a synergistic effect, which can not only reduce the cycle impedance of the lithium-ion battery and improve its cycle life, but also reduce the storage gas generation of the lithium-ion battery and improve its high-temperature storage performance, thereby meeting the application requirements of high-nickel and high-energy-density lithium-ion batteries;
[0047] (2) The lithium-ion battery prepared by the non-aqueous electrolyte provided by the present invention has good stability and safety. Its capacity retention rate under the test conditions of 25°C and 1C is 89.2-96.2%, and its capacity retention rate under the test conditions of 45°C and 1C is 79.4-89.4%. The volume expansion rate after storage for 28 days at 60 degrees Celsius is 5.5-8.5%. DETAILED DESCRIPTION
[0048] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0049] Some of the raw material information used in the following examples and comparative examples is as follows:
[0050] Additive A: (pentafluorophenyl) diphenylphosphine, CAS number 5525-95-1, molecular weight 352.238;
[0051] Additive B: Preparation method see Example 2 of CN116143666A;
[0052] Examples 1-20 and Comparative Examples 1-4
[0053] A non-aqueous electrolyte is provided, the composition of which is shown in Table 1.
[0054] The preparation method of the electrolyte is as follows:
[0055] The electrolyte (the filling gas is argon, and the gaseous water is less than 10 ppm) is prepared in a Michelona glove box. First, non-aqueous organic solvents such as ethylene carbonate (EC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and propylene carbonate (PC) are uniformly mixed in proportion and stored at low temperature (-10°C). Additive A, additive B and optional other additives are added to the uniformly mixed solvent package in sequence. Finally, LiPF6 and lithium salt additives are added and mixed until there is no lithium salt residue at the bottom and the electrolyte is clear and not turbid, so as to obtain an electrolyte with normal chromaticity, which is stored in a -10°C refrigerator.
[0056] Table 1
[0057]
[0058]
[0059]
[0060] In Table 1, “ / ” represents not added.
[0061] Application Example 1-20 and Comparative Application Example 1-4
[0062] In application examples 1-20 and comparative application examples 1-4, a lithium-ion battery is provided respectively, wherein the lithium-ion battery comprises a battery cell and an electrolyte, wherein the battery cell comprises a positive electrode, a negative electrode and a separator, and the electrolyte is the non-aqueous electrolyte provided in embodiments 1-20 and comparative examples 1-4 respectively.
[0063] The preparation method of a lithium-ion battery comprises the following steps:
[0064] (1) Preparation of positive electrode: Polyvinylidene fluoride (PVDF) was uniformly dissolved in N-methylpyrrolidone (NMP), and then the conductive agent Super P was added and mixed thoroughly. 0.8 Co 0.1 Mn 0.1 O2 powder is gradually added (LiNi 0.8 Co 0.1 Mn 0.1 The mass ratio of O2 powder, PVDF and conductive agent Super P is 97.4:1.3:1.3 to obtain positive electrode slurry (the output solid content of the positive electrode slurry is 63.1%), and the positive electrode slurry is coated on the current collector, and then dried, rolled and slit to obtain positive electrode sheets that can be directly stacked.
[0065] (2) Preparation of negative electrode: Graphite, conductive carbon, silicon oxide powder and sodium carboxymethyl cellulose in a mass ratio of 80.9:2.9:15:1.2 were pre-mixed and stirred at a speed of 250 rpm for 140 min to obtain a negative electrode slurry. The negative electrode slurry was then transferred to deionized water for dispersion. After mixing evenly, the negative electrode slurry was sieved (180 mesh). Finally, the sieved negative electrode slurry was coated on the negative electrode current collector, and then dried, rolled and slit to obtain a negative electrode sheet that can be directly laminated.
[0066] (3) Cell production: The positive and negative electrodes after stripping are stacked on a stacking machine. The separator is made of a three-layer material of PP / PE / PP to form a soft-pack cell.
[0067] (4) Liquid injection, formation and aging:
[0068] After the battery cell is dried at high temperature, the non-aqueous electrolyte of Examples 1-20 and Comparative Examples 1-4 is injected into the soft-pack battery cell. After the electrolyte is injected, the lithium battery is packaged for the first time, and the surface is cleaned and other processes are completed. It is placed at room temperature for one day. The formation is carried out by a step-by-step formation method. The first step is a formation current of 0.05C, and a constant current is charged for 2h. The second step is a formation current of 0.1C, and a constant current is charged until the voltage reaches 3.85V. After formation, it is aged at 50℃ for one day, cooled to room temperature, and finally sealed.
[0069] Performance test of lithium-ion batteries obtained from application examples 1-20 and comparative application examples 1-4
[0070] After the battery is assembled, place it in a room temperature for 10 hours to allow the non-aqueous electrolyte to fully penetrate the battery electrodes, and then test it according to the following method:
[0071] (1) 25℃ normal temperature cycle test: The battery is charged and discharged at a constant current density of 1C at rated capacity in a 25℃ constant temperature room for 1000 cycles. The test voltage range is 2.75V-4.2V and the charge cut-off current is 0.05C. After the test, the capacity retention rate at the 1000th week is calculated based on the discharge capacity in the first week.
[0072] The calculation formula for the capacity retention rate after 1000 cycles at room temperature is as follows:
[0073] 1000th cycle capacity retention rate (%) = (1000th room temperature cycle discharge capacity / first discharge capacity)*100%.
[0074] (2) 45°C high temperature cycle test: In a constant temperature 45°C forced air oven, constant current charge and discharge were performed at a current density of 1C at the rated capacity. The cycle number was 1000. The test voltage range was 2.75V-4.2V, and the charge cut-off current was 0.05C. After the test, the capacity retention rate at the 1000th week was calculated based on the discharge capacity in the first week.
[0075] The calculation formula for 1000-week high-temperature cycle capacity retention rate is as follows:
[0076] 1000th cycle capacity retention rate (%) = (1000th high-temperature cycle discharge capacity / first discharge capacity)*100%.
[0077] (3) Test of high-temperature gas production performance of lithium-ion batteries: Perform constant current charge and discharge at a current density of 1C at rated capacity in a constant temperature chamber at 25°C, and then charge at a constant voltage of 4.2V to a current of 0.05C. After the battery is fully charged, the initial volume of the battery is tested by the water discharge method. The battery is placed in an oven at 60°C for 7 days, and then the battery is taken out. It is left at room temperature for 60 minutes. After cooling to room temperature, the battery volume is tested by the water discharge method.
[0078] Carry out storage test according to the above steps until the storage is 28 days. Take the battery volume tested before storage as the benchmark and calculate the volume expansion rate of the battery as the storage time changes.
[0079] The volume expansion rate of high-temperature storage on the 28th day = (volume after high-temperature storage on the 28th day - initial volume of the battery / initial volume of the battery) * 100%.
[0080] The test results of application examples 1-20 and comparative application examples 1-4 are shown in Table 2.
[0081] Table 2
[0082]
[0083]
[0084] The test results show that:
[0085] (1) The electrolyte of the present invention, by adding additives A and additive B, enables the lithium ion battery to have a good room temperature capacity retention rate and a high high temperature capacity retention rate, and can greatly inhibit the volume expansion of the lithium ion battery during storage. It can be seen from Application Examples 1-20 that the lithium ion battery assembled with the non-aqueous electrolyte has a capacity retention rate of 89.2-96.2% under the test conditions of 25°C and 1C, a capacity retention rate of 79.4-89.4% under the test conditions of 45°C and 1C, and a volume expansion rate of 5.5-8.5% after storage for 28 days at 60°C.
[0086] (2) By comparing Application Example 1 with Application Examples 14-20, it can be seen that when the content of additive A is fixed, the present invention can enable the lithium-ion battery to obtain better high and low temperature cycle performance and high temperature storage performance by further limiting the content of additive B. When the mass ratio of additive A to additive B is (0.5-2.5):1, the non-aqueous electrolyte obtained has a better room temperature and high temperature capacity retention rate, and can greatly inhibit the volume expansion of the lithium-ion battery during storage; further, in combination with Application Examples 2-4, it can be seen that when the mass ratio of additive A to B in the non-aqueous electrolyte provided by the present invention is 1:1, the lithium-ion battery can have better high and low temperature cycle performance and high temperature storage performance.
[0087] (3) By comparing Application Example 1 with Comparative Application Example 1 and corresponding Examples 3 and 4, it can be seen that the present invention can reduce the cycle impedance of the lithium-ion battery and improve its cycle life by adding specific additives A and B to the non-aqueous electrolyte, and can also reduce the storage gas production of the lithium-ion battery and improve its high-temperature storage performance. That is, the synergistic effect of the two greatly improves the comprehensive performance of the obtained lithium-ion battery; while only adding a single additive A or additive B, although it can improve the high-temperature cycle performance of the battery and reduce its storage gas production to a certain extent, the single additive A or B cannot exert the synergistic effect of the two, and thus cannot significantly reduce the cycle impedance of the lithium-ion battery and improve its high-temperature storage performance.
[0088] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A non-aqueous electrolyte, characterized in that: The non-aqueous electrolyte includes an electrolyte, a non-aqueous organic solvent and an additive, wherein the additive includes an additive A and an additive B, wherein the additive A has a structure represented by Formula 1, and the additive B has a structure represented by Formula 2: The dotted lines represent the interactions between atoms.
2. The non-aqueous electrolyte according to claim 1, characterized in that The mass percentage of the electrolyte is 2-22% based on the mass of the non-aqueous electrolyte being 100%; Preferably, the electrolyte is a lithium salt; Preferably, the lithium salt comprises lithium hexafluorophosphate.
3. The non-aqueous electrolyte according to claim 1 or 2, characterized in that Taking the mass of the non-aqueous electrolyte as 100%, the mass percentage of the non-aqueous organic solvent is 75-94%; Preferably, the non-aqueous organic solvent comprises a carbonate organic solvent and / or a carboxylate organic solvent; Preferably, the carbonate organic solvent includes cyclic carbonate and / or chain carbonate; Preferably, the cyclic carbonate includes any one of ethylene carbonate, propylene carbonate or butylene carbonate or a combination of at least two thereof; Preferably, the linear carbonate comprises any one of diethyl carbonate, ethyl methyl carbonate, dimethyl carbonate or methyl propyl carbonate, or a combination of at least two thereof; Preferably, the carboxylate organic solvent includes any one of ethyl propionate, propyl propionate, ethyl acetate, ethyl butyrate, methyl acetate, propyl acetate, methyl propionate or γ-butyrolactone, or a combination of at least two thereof.
4. The non-aqueous electrolyte according to any one of claims 1 to 3, characterized in that: Based on the mass of the non-aqueous electrolyte being 100%, the mass percentage of the additive A is 0.2-4%, preferably 0.2-2%.
5. The non-aqueous electrolyte according to any one of claims 1 to 4, characterized in that: Based on the mass of the non-aqueous electrolyte being 100%, the mass percentage of the additive B is 0.2-4%, preferably 0.2-2%.
6. The non-aqueous electrolyte according to any one of claims 1 to 5, characterized in that: The additives also include lithium salt additives; Preferably, based on the mass of the non-aqueous electrolyte being 100%, the mass percentage of the lithium salt additive is 0.2-3.0%; Preferably, the lithium salt additive includes any one of lithium difluorosulfonate imide, lithium difluorooxalatoborate, lithium tetrafluoroborate, bisoxalatoborate, lithium difluorophosphate or lithium difluorobisoxalatophosphate, or a combination of at least two thereof.
7. The non-aqueous electrolyte according to any one of claims 1 to 6, characterized in that: The additives include other additives; Preferably, based on the mass of the non-aqueous electrolyte being 100%, the mass percentage of the other additives is 0.5-11.6%; Preferably, the other additives include any one or a combination of at least two of vinylene carbonate, 1,3-propane sultone, fluoroethylene carbonate, vinyl ethylene sulfate, vinyl sulfate, methylene methanedisulfonate, vinylene carbonate, tris(trimethylsilane) phosphate, and tris(trimethylsilane) borate.
8. A lithium ion battery, characterized in that: The lithium-ion battery comprises a battery cell and an electrolyte, wherein the battery cell comprises a positive electrode, a negative electrode and a separator, wherein the separator is disposed between the positive electrode and the negative electrode, and the electrolyte is the non-aqueous electrolyte according to any one of claims 1 to 7; Preferably, the positive electrode comprises a positive electrode active material, a conductive agent and a binder; Preferably, the negative electrode plate comprises a negative electrode active material; Preferably, the material of the diaphragm includes any one of polyethylene, polypropylene or a composite ceramic membrane, or a combination of at least two of them.
9. The lithium-ion battery according to claim 8, characterized in that: The positive electrode active material includes LiNi x Co y Mn z L (1-x-y-z) O2 and / or LiNi x' L' y' Mn (2-x'-y') O4; Wherein, L is any one of Al, Sr, Mg, Ti, Ca, Zr, Zn, Si or Fe, or a combination of at least two thereof; 0.5≤x≤1, 0≤y<1, 0≤z≤1, 0<x+y+z≤1, 0<x'≤1, 0.01≤y'≤0.2; L' is any one of Co, Al, Sr, Mg, Ti, Ca, Zr, Zn, Si or Fe, or a combination of at least two thereof.
10. The lithium ion battery according to claim 8 or 9, characterized in that: The negative electrode active material includes any one of natural graphite, artificial graphite, soft carbon, hard carbon, mesophase carbon microspheres, graphene, graphyne, metallic lithium, nanocarbon, carbon nanotubes, elemental silicon, silicon oxide compounds, silicon / copper oxide complexes, AG complexes, silicon alloys, elemental tin, tin oxide compounds, tin-carbon complexes, tin alloys or lithium titanate, or a combination of at least two thereof.
